EKSISTENSI PENGELOLAAN TATA USAHA PADA LEMBAGA TINGGI SWASTA - Agus Fahmi (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2020)
The academic management system at Tertiary Education Institutions is the core of the implementation of Higher Education activities that regulate all matters including the effectiveness of implementation, information, service quality, and efficient use of resources. Management strategy is a process or series of decision-making activities that are fundamental and comprehensive, accompanied by determining how to carry it out, which is made by the leadership and implemented by all levels in an organization to achieve goals. In the implementation of Private Higher Education (PTS) it is imperative that the quality of academic services be carried out in a directed, disciplined manner, with total quality, and ensures the realization of the quality of higher education properly. So far, many higher education institutions, especially private universities, have always put aside academic services, even only as a symbol for academic services within the institution. In fact, when viewed from various perspectives it is common knowledge that effective academic services will have a positive effect on the quality of the institution. Therefore it is very important to determine a strategy that supports the achievement of goals, because strategic is a large-scale planning (called strategic planning) that is oriented towards a far-reaching future (called a vision), and is determined as the decision of the highest leadership (decisions that are fundamental and principle), in order to enable the organization to interact effectively (called a mission), in an effort to produce something (operational planning to produce goods and / or services and services) of quality, directed at optimizing the achievement of goals (called strategic objectives) and various objectives (operational objectives). ) organization (Nawawi, 2003). Keywords: Existence Management, Private College